Effects of salicylic acid pre-treatment on cadmium and/or UV-B stress in soybean seedlings - X. M. Li; L. J. Ma; N. Bu; Y. Y. Li; L. H. Zhang (Biologia Plantarum, 2014)
The present study examined the effect of salicylic acid (SA) pre-treatment on soybean seedlings exposed to cadmium and/or UV-B stress. Dry mass, pigment content, net photosynthetic rate (PN), stomatal conductance (gs), and transpiration rate (E) were decreased by the Cd and/or UV-B stress. SA alleviated the adverse effects of Cd and/or UV-B on growth, pigment content, PN, and gs, but did not mitigate the inhibitory effect of Cd/UV-B on E, or that of Cd on chlorophyll fluorescence parameters. Cd and/or UV-B induced oxidative stress and increased lipid peroxidation that was significantly decreased by SA pre-treatment. The Cd and/or UV-B increased superoxide dismutase (SOD) activity, decreased peroxidase (POD) activity, and catalase (CAT) activity was mostly unaltered. SA might act as one of the potential antioxidants as well as a stabilizer of membrane integrity to improve plant resistance to the Cd and/or UV-B stress.